2002
DOI: 10.1093/tropej/48.4.210
|View full text |Cite
|
Sign up to set email alerts
|

Changing Spectrum of Sporadic Acute Viral Hepatitis in Indian Children

Abstract: From August 1997 to January 2000, 172 children (< or = 14 years) with acute viral hepatitis were studied. Their clinical features, investigations and outcome were noted. Viral markers (IgM anti-HAV, IgM anti-HEV, HBsAg and anti-HCV) were measured by ELISA using commercial kits. The mean age of these children was 5.6 +/- 2.9 (range, 4 months to 14 years) with a male to female ratio of 120:52. Prodromal symptoms were present in 161 (94 per cent) and icteric hepatitis was diagnosed in 168 (98 per cent) cases. Spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
55
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 0 publications
14
55
1
3
Order By: Relevance
“…Studies have previously documented a variable prevalence of hepatotropic viruses: Hepatitis A Virus (HAV) (1.7-67%), Hepatitis B Virus (HBV) (7.3-42%), Hepatitis C Virus (HCV) (1.16-10.6%) and HEV (Hepatitis E Virus) (16.3-66.3%) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have previously documented a variable prevalence of hepatotropic viruses: Hepatitis A Virus (HAV) (1.7-67%), Hepatitis B Virus (HBV) (7.3-42%), Hepatitis C Virus (HCV) (1.16-10.6%) and HEV (Hepatitis E Virus) (16.3-66.3%) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although a slight preponderance of male as compared to females which was different from Poddar U et al study, spectrum of sporadic acute viral hepatitis in Indian children where they found that male to female ratio of 2.3:1. 13 It however would be difficult to conclude whether this disease shows any predilection for either sex.…”
Section: Discussionmentioning
confidence: 99%
“…Chadha et al from Pune reported HBV as a cause for 5.4% of acute viral hepatitis cases ; similarly in studies from New Delhi in 1984 and 2002 the rates were 9% and 7.6% respectively; also from Lucknow, the rate was 9.79%. 3,[6][7][8] Study done from Hong Kong showed incidence of HBV to be 8% of all acute viral hepatitis in children less than 12 years. 9 From Kathmandu, Nepal HBV was responsible for 5% of causes of acute hepatitis in children under 15 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…4 In 2002, study from Chandigarh done on children under 14 years showed HBV responsible for 7.6% of acute viral hepatitis. 5 Genetic factors and host susceptibility affects the persistent carriage stage of Australia antigen. This study tries to assess the incidence of acute hepatitis caused by hepatitis B virus and analyses the LFTs for early diagnosis and severity of acute hepatitis.…”
Section: Introductionmentioning
confidence: 99%